Academic Procrastination of Bekasi City Students during the Covid-19 Pandemic - Novitasari, Yussie; Prihantoro, Edy (Technium Social Sciences Journal, 2023)
This research was conducted because the phenomenon of academic procrastination is a common thing and almost every student has done it. During the COVID-19 Pandemic, all Teaching and Learning Activities (KBM) were conducted online, resulting in higher levels of academic procrastination. The purpose of this study was to determine the level of academic procrastination of Bekasi City Vocational High School (SMK) students during the COVID-19 pandemic and what efforts were made by the school to overcome it. The research approach used is qualitative with Field Research (Field Research). The informants in this study included: Vocational High School students, Regional III Branch Office Staff, Vocational Supervisors, Vocational School Principals, Vocational Productive Subject Teachers, and Parents of Vocational School Students in Bekasi City. Data collection by interview technique, while the discussion using descriptive method that describes the situation in the field systematically. The results showed that the academic procrastination of Bekasi City Vocational High School students experienced an increase during learning during the COVID-19 Pandemic, including: Delays in starting and completing assignments; Delay in completing tasks; Time gap between planned and actual performance; and engage in more enjoyable activities. Countermeasures carried out by the school include: Providing interesting learning materials; Provide deadlines for each task; Conduct intensive communication with students and parents as well as conduct home visits for students with problems.